Tunable optical and photovoltaic performance in PTB7-based colored semi-transparent organic solar cells integrated MgF2/WO3 1D-photonic crystals via advanced light management - Erman Cokduygulular; Caglar Cetinkaya; Serkan Emik; Baris Kinaci (Scientific Reports)
Abstract This study explores the design, fabrication, and characterization of PTB7-based colored semi-transparent organic solar cells (ST-OSCs) with integrated MgF2/WO3 one-dimensional photonic crystals (1D-PCs). Integrating 1D-PCs enhanced light management by creating tunable photonic band gaps, leading to extraordinary color change and improved photon harvesting. For 1DPC5 − 425 the Average Visible Transmittance (AVT) values were 33.3%, and CIE x, y was 0.43, 0.52, for 1DPC3 − 650 AVT were 25.09% and CIE x, y was 0.23, 0.27, respectively. Thus, extraordinary color changes from blue to yellow could be achieved while keeping transparency. Thereupon, photovoltaic performance showed notable improvements, with Jsc increasing from 7.98 mA/cm2 to 9.95 mA/cm2 and 10.45 mA/cm2 for 1DPC5 − 425 and 1DPC3 − 650, respectively. By 1D-PC integration, power conversion efficiency (PCE) reached from 3.93 to 4.90% and 5.08% for 1DPC5 − 425 and 1DPC3 − 650, respectively. The Color Rendering Index (CRI) indicated successful color tuning and acceptable rendering, with CRI of 52 and 87. The study demonstrates that 1D-PC integration significantly enhances ST-OSCs’ optical and photovoltaic properties, paving the way for advanced energy-harvesting applications.